Implementation of a new Preference Based Final Year Project title selection system for undergraduate engineering students in UNITEN - Hasan M.H.; Mohamed Sahari K.S.; Anuar A. (2023)
The department of Mechanical Engineering in Universiti Tenaga Nasional decided to test and implement a new Final Year Project title selection system because of perceived weaknesses in the existing system which employs a first come first served mechanism to allocate titles to students. The new system, dubbed the Preference Based system, uses a computer algorithm to allocate titles to students based on students' submissions of their 10 most preferred titles in order of preference. Three algorithms were developed for this allocation purpose, and they were evaluated by calculation and comparison of the costs of their selection. The Network Flow Optimization algorithm, which was able to produce a selection with the lowest cost, was selected and used to allocate titles for students from Semester 1 of the 2009/2010 academic year. The algorithm was able to ensure that each student got one of their 10 preferred titles and 78.5% of the students got titles that were ranked in their top 3. A survey carried out after the selection exercise confirmed the students' satisfaction and preference of the new system over the previous first come first served system. 2009 IEEE.